Persistent bacteremia predicts poor outcomes among neutropenic patients with carbapenem-resistant gram-negative bloodstream infections receiving appropriate therapy - Abi Manesh Sathya Kumar; Mithun Mohan George; Kundakarla Bhanuprasad; Grace Mary John; Anu Korula; Aby Abraham; Vikram Mathews; Uday Prakash Kulkarni; Chaitra Shankar; Prasanna Samuel Premkumar; Binila Chacko; K. Subramani; et al. (BMC, 2023)
Abstract Purpose Identifying persistent bacteremia early in patients with neutropenia may improve outcome. This study evaluated the role of follow-up blood cultures (FUBC) positivity in predicting outcomes among patients with neutropenia and carbapenem-resistant gram-negative bloodstream infections (CRGNBSI). Methods This retrospective cohort study conducted between December 2017 and April 2022 included patients more than 15 years old with neutropenia and CRGNBSI, who survived for ≥ 48 h, receiving appropriate antibiotic therapy and had FUBCs. Patients with polymicrobial bacteremia within 30 days were excluded. The primary outcome was 30 day mortality. Persistent bacteremia, septic shock, recovery from neutropenia, prolonged or profound neutropenia, requirement of intensive care and dialysis, and initiation of appropriate empirical therapy were also studied. Results In our study cohort of 155 patients, the 30 day mortality rate was 47.7%. Persistent bacteremia was common in our patient cohort (43.8%). Carbapenem resistant isolates identified in the study were K.pneumoniae (80%), E.coli (12.26%), P.aeruginosa (5.16%), A.baumanii (1.94%) and E.cloacae (0.65%). The median time for sending a FUBC was 2 days (IQR, 1-3 days). Patients with persistent bacteremia had higher mortality than those without (56.76% versus 32.1%; p < 0.001). Appropriate initial empirical therapy was given to 70.9%. Recovery from neutropenia occurred in 57.4% while 25.8% had prolonged or profound neutropenia. Sixty-nine percent (107/155) had septic shock and needed intensive care; 12.2% of patients required dialysis. Non-recovery from neutropenia (aHR, 4.28; 95% CI 2.53-7.23), presence of septic shock (aHR, 4.42; 95%CI 1.47-13.28), requirement of intensive care (aHR,3.12;95%CI 1.23-7.93), and persistent bacteremia (aHR,1.74; 95%CI 1.05-2.89) significantly predicted poor outcomes in multivariable analysis. Conclusion FUBC showing persistent bacteremia predicted poor outcomes among neutropenic patients with carbapenem-resistant gram-negative bloodstream infections (CRGNBSI) and should be routinely reported.